2019
DOI: 10.2188/jea.je20170280
|View full text |Cite
|
Sign up to set email alerts
|

Physical Fitness Tests and Type 2 Diabetes Among Japanese: A Longitudinal Study From the Niigata Wellness Study

Abstract: The performance of a simple single-leg balance test as well as that of a grip strength test were negatively associated with the risk of T2DM among Japanese.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 37 publications
3
49
0
Order By: Relevance
“…However, the mechanism of the potential association between frailty and incident dementia is unclear. It has been shown that physical frailty increases the risk of diabetes mellitus and cardiovascular disease [15,16]. Moreover, a clinical-pathologic study found physical frailty to be associated with dementia pathology [17][18][19], and alterations in hippocampal synaptic function, neuronal membrane properties, and axonal trajectories, which might lead to dementia have been reported for people with frailty [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanism of the potential association between frailty and incident dementia is unclear. It has been shown that physical frailty increases the risk of diabetes mellitus and cardiovascular disease [15,16]. Moreover, a clinical-pathologic study found physical frailty to be associated with dementia pathology [17][18][19], and alterations in hippocampal synaptic function, neuronal membrane properties, and axonal trajectories, which might lead to dementia have been reported for people with frailty [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Handgrip strength is an easy, non-invasive, and inexpensive measure of muscle strength in the elderly, which has been reported to be well-correlated with the muscle strength of limbs and the human trunk. 8,9 Additionally, it has been reported that lower handgrip strength is associated with a greater risk of diabetes mellitus, 10 cardiovascular disease, all-cause and cardiovascular mortality, and physical function and frailty. 11,12 Several population-based studies have also shown that reduced handgrip strength in late life was associated with increased risks of cognitive impairment and dementia.…”
Section: Introductionmentioning
confidence: 99%
“…We did not nd any relationship between the vertical jump test (power) or the step-test (endurance) and the risk of LS. Although the vertical jump test also shares characteristics in common with lower extremity strength, the vertical jump test does not only measure lower extremity strength, it also depends on speed (instantaneous power) [30,31]. The step-tests assesses the ability to perform a speci c muscular action for a prolonged period of time, and not just a bout of lower extremity strength [31].…”
Section: Discussionmentioning
confidence: 99%
“…Although the vertical jump test also shares characteristics in common with lower extremity strength, the vertical jump test does not only measure lower extremity strength, it also depends on speed (instantaneous power) [30,31]. The step-tests assesses the ability to perform a speci c muscular action for a prolonged period of time, and not just a bout of lower extremity strength [31]. Meanwhile, the LS is identi ed as a condition in which mobility functions such as sit-tostand or gait are reduced as a result of locomotive organ/system impairment [1].…”
Section: Discussionmentioning
confidence: 99%